Conservation management plan for sirpur, Chhattisgarh - Kumar Tode, Pranay (SPA Bhopal, 2018)
Archaeological discoveries and excavation at Sirpur, (a small village, spread over an area around 3.2 Sq. Kms, situated on the banks of river Mahanadi in Mahasamund District of Chhattisgarh), has attracted the attention of many researchers and excavators including the conservation architects and historians. There are still several unexcavated mounds in Sirpur that are under research and conceptual discovery of the ancient human settlement, infrastructure and natural setting. Based on various documents, drafts and books that mentions about Sirpur, it is moreover clear that Sirpur was named after the name of an Indian goddess Lakshmi and previously known as Shripur (Shreepur), where according to Hindu mythology Shri, that resembles the synonym for, the goddess of abundance, richness and auspiciousness. During the reign of Panduvamsis and Sarabhapuriyas, Sirpur was known as the central power of southern Kholsas in around 6th to 8th century AD. The Village became a centre of attraction and counted amongst one of the major archaeological site during 1882 after the visit of Alexander Cunningham an official of colonial British India. This site consists of several archaeological remains of 6th to 8th century A.D. that comprises Buddhist and Hindu structures both in the form of temples, monasteries and other unidentified ruins. The most celebrated structure of Sirpur, Laxman (Lakshmana) temple and Cunningham’s report brought Sirpur in to an international recognition. The exploration and excavation works resumed in 1953 as the got completely neglected during the season of world wars. This research focuses on the documentation and conservation management plan of Sirpur, attaining the solution for the issues observed within the site and synchronizing the proposals for the best resultant output that may enhance the historic values and awareness amongst the tourist and help several other researchers for further scope.
Keywords: MCO